Intraoperative radiotherapy: An alternative to whole‐breast external beam radiotherapy in the management of highly selective breast cancer: A SEER database analysis - Dexun Sun; Guanhua Lu; Fenmei Liang; Wangjian Zhang; Tao Zeng; Yun Ling; Haojie Peng; Ting Xia; Meilin Hu; Xinxin Chen (Cancer Medicine)
Abstract Objective This study aimed to verify if intraoperative radiotherapy (IORT) can achieve the same survival outcome as whole‐breast external beam radiotherapy (EBRT) in early breast cancer after breast‐conserving surgery (BCS), and to explore the suitable candidates that can safely receive IORT after BCS. Methods Eligible post‐BCS patients who received IORT or EBRT were included in the Surveillance, Epidemiology and End Results (SEER) database from 2010 to 2018. Risk factors that affected 5‐year overall survival (OS) or breast cancer specific survival (BCSS) were identified by Cox proportional hazards regression analysis. Clinical characteristics, OS, and BCSS were comparatively analyzed between the two treatment modalities. Results The survival analysis after propensity score matching confirmed that patients who received IORT (n = 2200) had a better 5‐year OS than those who received EBRT (n = 2200) (p = 0.015). However, the two groups did not differ significantly in 5‐year BCSS (p = 0.381). This feature persisted even after multivariate analyses that took into account numerous clinical characteristics. Although there was no significant difference in BCSS between different subgroups of patients treated with IORT or EBRT, patients over 55 years of age, with T1, N0, non‐triple negative breast cancers, hormone receptor‐positive, and histologic grade II showed a better OS after receiving IORT. Conclusion In low‐risk, early‐stage breast cancer, IORT was not inferior to EBRT considering 5‐year BCSS and OS. Considering the equivalent clinical outcome but less radiotoxicity, IORT might be a reasonable alternative to EBRT in highly selective patients undergoing BCS.